Pantalar arthrodesis in a case of chronic subluxated tibiotalar and subtalar joint with secondary arthritis: a case report - Garg, Bipul Kumar; Dave, Harshit (International Journal of Research in Orthopaedics, 2019)
Post-traumatic arthritis is the most common cause of ankle arthritis. Pantalar arthrodesis (PA) is a salvage operation that can be used to create a stable and functional plantigrade foot for those who have a painful ankle joint with significant bony destruction and/or malalignment of ankle and hindfoot producing deformities and instabilities not amenable to bracing, orthotic devices or shoes. It is commonly performed as a double staged procedure. We present a case of 50 years old male with chronic subluxated tibiotalar and subtalar joint with secondary arthritis who was operated with a single staged pantalar arthrodesis with a follow up of 6 months. A single staged Pantalar arthrodesis combining both transfibular approach for ankle and olliers approach for triple arthrodesis is an effective surgical treatment option in a case of chronic subluxated tibiotalar and subtalar joint with secondary arthritis.